Systematic Literature Review: Factors Affecting the Quality of Health Data Management - Muhammad Reyzaldy Rahim; Sri Astuti (PROMOTOR, 2026)
The quality of health data management is a crucial factor in supporting the effectiveness of healthcare services, clinical decision-making, and improving the quality of care in healthcare facilities. Digital transformation through the implementation of Electronic Medical Records (EMDRs) demands accurate, complete, secure, and integrated health data management. However, various healthcare facilities still face challenges in managing health data, such as limited human resources, technological infrastructure, and the quality of health information systems. This study aims to identify and analyze factors influencing the quality of health data management based on the latest research findings. The research method used a Systematic Literature Review (SLR) approach by examining quantitative journal articles published between 2022 and 2025. Articles were searched through several scientific databases using keywords related to health data management, electronic medical records, health data quality, and health information systems. Articles were selected based on inclusion and exclusion criteria relevant to the research objectives. A total of eight journals that met the criteria were systematically analyzed to obtain a synthesis of the research findings. The review results indicate that the quality of health data management is influenced by several key factors: the quality of the health information system, the implementation of Electronic Medical Records (EMR), human resource competency, completeness of documentation, technological infrastructure, data security, management support, and compliance with standard operating procedures and health regulations. The implementation of digital systems has been proven to improve service efficiency, data accuracy, patient information security, and the effectiveness of clinical decision-making. However, various obstacles remain, such as limited technological facilities, lack of human resource training, and obstacles to adapting to digital transformation. The study concludes that the quality of health data management requires strengthening the integrated aspects of technology, human resources, organization, and regulations. Improving the quality of health data management is expected to support the creation of more effective, efficient, safe, and sustainable health services.